A novel weighted sum method to measure particle geometric surface area in real-time. (March 2018) - Cao, Leo N.Y.; Pui, David Y.H.
Abstract: This paper reports the development of a novel method to measure the aerosol geometric surface area (GSA) concentration with a time resolution of a few seconds. In the method, the commercialized nanoparticle surface area monitor was used and slightly modified. The instrument responses under two different conditions were combined in a weighted sum (WS) fashion to correlate with the aerosol GSA concentration. We present the GSA concentration results and comparisons with well-known SMPS data in both laboratory testing and field measurement. For the laboratory testing, the two methods have a good agreement with a Pearson correlation coefficient of 0.9961; for the field measurements including the indoor and outdoor samplings, both methods agree well with each other. In addition, the new WS method is more stable in the clean indoor air and suitable for outdoor environmental sampling with a slight overestimation (125% of SMPS). Highlights: The instrument responses were combined in a weighted sum (WS) fashion. The cost-effective WS method delivers real-time measurements of particle geometric surface area concentration. The WS method has a wide working range from 20 to 300 nm. The WS method was validated by both synthetic and environmental aerosols.